2016
DOI: 10.1111/hsc.12404
|View full text |Cite
|
Sign up to set email alerts
|

How do frequent users of crisis helplines differ from other users regarding their reasons for calling? Results from a survey with callers to Lifeline, Australia's national crisis helpline service

Abstract: Crisis helplines are designed to provide short-term support to people in an immediate crisis. However, there is a group of users who call crisis helplines frequently over an extended period of time. The reasons for their ongoing use remain unclear. The aim of this study was to investigate the differences in the reasons for calling between frequent and other users of crisis helplines. This was achieved by examining the findings from a brief survey completed by callers to Lifeline Australia at the end of their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
2
22
1
Order By: Relevance
“…These studies also identified factors that drive frequent callers to call the service: positive reinforcement, social isolation of the caller, service maintaining anonymity of the caller and unrestricted access to the service. 6,7 Helplines Partnership identified a trend of increasing demand in UK helplines year on year. 5 Samaritans Ireland reported a 60 per cent increase in demand when they moved to a free phone number in 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also identified factors that drive frequent callers to call the service: positive reinforcement, social isolation of the caller, service maintaining anonymity of the caller and unrestricted access to the service. 6,7 Helplines Partnership identified a trend of increasing demand in UK helplines year on year. 5 Samaritans Ireland reported a 60 per cent increase in demand when they moved to a free phone number in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also identified factors that drive frequent callers to call the service: positive reinforcement, social isolation of the caller, service maintaining anonymity of the caller and unrestricted access to the service. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…These services are now an integral part of community crisis support services in Australia (Gould et al, 2012), and the role of these services has expanded beyond the provision of one-time interventions to encompass the facilitation of longer-term interventions-for instance, by connecting callers to traditional mental health services and/or emergency healthcare services (Middleton et al, 2017). Crisis helpline workers are trained to deliver interventions in a time-and information-limited context.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research points to the efficacy of these services in helping callers cope during a time of personal crisis (see: Assing-Hvidt et al, 2016;Dadfar & Lester, 2019;Dong et al, 2016;Kitchingman et al, 2015;Kitchingman et al, 2016). Furthermore, the experiences of specific groups have received considerable attention -among them: men , the elderly people (Chan et al, 2018), frequent callers (Middleton et al, 2017;Spittal et al, 2015) and helpline workers themselves Kitchingman et al, 2017aKitchingman et al, , 2017bSundram et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite such challenges, some research has successfully evaluated characteristics of frequent callers through unique data methods or follow up surveys. This research has identified that 2.6% to 22% of all calls are from frequent callers and has described common characteristics of frequent callers, such as calling about domestic violence and child protection, as well as having high-risk presentations (Middleton et al, 2017;O'Neill et al, 2019;Spittal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%